Slum Upgrading in Cengkareng, West Jakarta - Saipiatuddin; Hidayaht, Achmad Nur; Kurniawan, Nandi (Journal of Geography Science and Education, 2024)
This research aims to evaluate the level of slum conditions in Cengkareng Subdistrict and identify suitable upgrading alternatives to address the situation. The assessment method used is scoring/weighting based on the Guidelines for PU Cipta Karya to measure the level of slum conditions, and the Analytic Hierarchy Process (AHP) method to determine slum upgrading. This strategy is based on best practices taken from the Book of CODI updates with a focus on Community Upgrading Projects published by the Community Organizations Development Institute in Thailand. The study results indicate that there are three levels of slum conditions in Cengkareng Subdistrict, namely, light, moderate, and severe slums. For alternative rejuvenation strategies, on-site upgrading is chosen for low and moderate slum levels, while on-site reblocking is selected for areas with a very severe slum condition.